Cytokine and angiogenic factors associated with efficacy and toxicity of pazopanib in advanced soft-tissue sarcoma: an EORTC-STBSG study - Sleijfer, Stefan; Hohenberger, Peter (British journal of cancer, 2012)
Background:Pazopanib has activity in relapsed non-adipocytic soft-tissue sarcomas (STS). A series of serum cytokines and angiogenic factors (CAFs) at baseline and changes in soluble vascular endothelial growth factor receptor-2 (sVEGFR2) or placental-derived growth factor (PlGF) levels during treatment were explored for their association with outcome.Methods:Twenty-three baseline CAFs, and sVEGFR2 and PlGF changes were measured in 85 and 32 patients, respectively. Associations between baseline CAF levels and efficacy parameters, plus between-week 12 sVEGFR2 and PlGF levels and pazopanib-specific toxicities were investigated.Results:At baseline, low interleukin (IL)-12 p40 subunit and MPC3 levels were associated with better progression-free survival (PFS) at 12 weeks (PFS12wks), low basic nerve growth factor and hepatocyte growth factor with a better PFS, and low inter-cellular adhesion molecule-1 and IL-2 receptor alpha with prolonged overall survival (OS; all P<0.05). Pazopanib decreased sVEGFR2 and increased PlGF levels. Low sVEGFR2 and high PlGF levels at week 12 were associated with higher-grade hypertension, with TSH elevations and with poorer PFS12wks, and OS (both P<0.05).Conclusion:Several baseline CAFs were related to outcome parameters. Low sVEGFR2 and high PlGF at week 12 associate with several pazopanib-specific toxicities and poorer efficacy. If confirmed, these factors may be used as early markers for response to and toxicity from pazopanib, enabling further individualisation of STS treatment.
Gesehen am 18.10.2018